THE PUBLIC ATTITUDE TOWARDS THE PROBLEMS OF PEOPLE WITH DISABILITIES AND THEIR READINESS FOR INTEGRATION THROUGH EMPLOYMENT - P. Stoevska (Trakia Journal of Sciences)
The focus of this article is on the attitudes of different social groups towards the problems of people with disabilities and their willingness to assist in the processes of their integration through work. For this purpose an empirical survey was conducted in the period October - December 2019 through anonymous paper and electronic questionnaires, including 28 questions, grouped in 5 sections. The survey covers 250 participants from across the country at different ages and with different sociodemographic profiles. The data are processed by the methods of descriptive statistics, as well as onedimensional and two-dimensional frequency analysis. The survey shows that a significant proportion of respondents demonstrate an understanding of the problems of people with disabilities, a willingness to help overcome the negative stereotypes towards disabled people with regard to their inclusion in the labor market. On the other hand, the general public is not sufficiently informed about the efforts of the government sector, human rights and non-governmental organizations on the labor integration of this vulnerable group, due to insufficient promotion of legislative and regulatory changes and their practical application in this field of social policy of the state. Another finding from the empirical study is that the opportunities for integration of persons with disabilities through work are not guaranteed both because of their lack of initiative and due to the existing manifestations of discrimination by some employers in the employment of persons with disabilities.